Crop management systems and maize grain yield under narrow row spacing - Strieder M.L. (2008)
Reduction in row spacing provides a more uniform distribution among plants that can increase grain yield. The benefits of narrow row spacing can depend on the plant architecture and on the kind of crop management system. The objective of this study was to assess the effects of narrow row spacing on the grain yield of maize hybrids growing under different management systems. Six experiments were carried out in Eldorado do Sul, State of Rio Grande do Sul, Brazil, during the 2003/04 and 2004/05 growing seasons. Each experiment corresponded to a crop management system. Treatments consisted of two row spacings (0.8 and 0.4 m), two hybrids (Penta and Flash) and two plant densities, which varied with the crop management system and growing season. Besides plant density, the crop management systems differed in the quantities of fertilizers applied at sowing, side-dress and use of irrigation. A complete randomized block design was used in each experiment, in a 2 x 2 x 2 treatment factorial scheme with four replications. The increases in grain yield with narrow row spacing were small, ranging from zero to 14%. They depended on the growing season and were manifested only with yields higher than 10 t ha-1, regardless of the hybrid. The number of grains per area was the component that best explained the response of grain to narrow row spacing, regardless of plant density, hybrid and crop management system. Narrow row spacing is a worth management strategy to enhance maize grain yield when high input cropping systems are used.